2006
DOI: 10.1093/eurheartj/ehl307
|View full text |Cite
|
Sign up to set email alerts
|

Is inducibility of atrial fibrillation after radio frequency ablation really a relevant prognostic factor?

Abstract: Aims The study was intended to assess the prognostic value of inducibility of atrial fibrillation (AF) after radio frequency ablation. Methods and results Two hundred and thirty four patients with drug-resistant paroxysmal (n ¼ 165) or persistent AF (n ¼ 69) underwent either Lasso-guided segmental pulmonary vein isolation (n ¼ 83) or CARTO-guided left atrial circumferential ablation (n ¼ 151). After ablation, two attempts to induce AF (.1 min) by decremental coronary sinus stimulation were performed. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 31 publications
(33 reference statements)
6
87
6
Order By: Relevance
“…268,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298 A recent meta-analysis identified 16 studies involving 5864 individuals reporting on the link between obesity and recurrence of AF after catheter ablation, identifying that there was a 3.1% greater risk of recurrent AF postablation for every one unit increase in BMI (RR 1.03; 95% CI 1.00–1.07). 299 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…268,282,283,284,285,286,287,288,289,290,291,292,293,294,295,296,297,298 A recent meta-analysis identified 16 studies involving 5864 individuals reporting on the link between obesity and recurrence of AF after catheter ablation, identifying that there was a 3.1% greater risk of recurrent AF postablation for every one unit increase in BMI (RR 1.03; 95% CI 1.00–1.07). 299 …”
Section: Section 3: Modifiable Risk Factors For Af and Impact On Ablamentioning
confidence: 99%
“…Noninducibility of atrial tachyarrhythmia was defined if it terminated within 5 minutes. 16 The inducibility test was performed either after completion of PVI in patients with termination of atrial tachyarrhythmia or each time atrial tachyarrhythmia was terminated during additional post-PVI ablation in patients who experienced sustained atrial tachyarrhythmia after PVI. A stepwise procedure was applied to achieve noninducibility.…”
Section: Electrophysiological Study and Ablation Proceduresmentioning
confidence: 99%
“…16,[19][20][21][22][23][24][25][26][27][28] Noninducibility of AF achieved by additional ablation after PVI is associated with lower AF recurrence compared with PVI alone. 23,24,28 However, Leong-Sit 29 et al reported that noninducibility of any atrial tachyarrhythmia is not predictive of clinical recurrence at a 1-year follow-up.…”
Section: Need For An Additional Procedural End Point Beyond Pvimentioning
confidence: 99%
“…Patients with inducible AF are at an increased risk of AF recurrence, even after pulmonary vein isolation [8,9]. Atrial effective refractory periods (ERP) and its spatial dispersion heterogeneity have been accepted to promote AF re-initiation and to provide a substrate for the re-entry of multiple wavelets to enhance the ability of the disorder to sustaining itself [10,11].…”
Section: Introductionmentioning
confidence: 99%